The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2015
DOI: 10.1089/cyber.2014.0479
|View full text |Cite
|
Sign up to set email alerts
|

Snapchat Elicits More Jealousy than Facebook: A Comparison of Snapchat and Facebook Use

Abstract: Recent news in the media has suggested that younger people are using popular social media such as Facebook less and are quickly adopting newer media, such as the self-destructing app Snapchat. Snapchat is unique in that it erases messages several seconds after they have been sent, affording its users a higher level of privacy. Yet, little research exists on Snapchat use in general, let alone its broader psychological implications. This article offers a preliminary comparison of Snapchat and Facebook use and ps… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

9
122
0
6

Year Published

2017
2017
2023
2023

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 201 publications
(137 citation statements)
references
References 19 publications
9
122
0
6
Order By: Relevance
“…Utz et al's (2015) study of jealousy and Snapchat affirms the popular opinion that Snapchat's ephemerality, as well as its privacy, are key drivers for flirtatious or sexual communications.…”
Section: Stories Snaps and Screenshots: What Is Snapchat?mentioning
confidence: 66%
See 2 more Smart Citations
“…Utz et al's (2015) study of jealousy and Snapchat affirms the popular opinion that Snapchat's ephemerality, as well as its privacy, are key drivers for flirtatious or sexual communications.…”
Section: Stories Snaps and Screenshots: What Is Snapchat?mentioning
confidence: 66%
“…(CNN, January 2013) and 'Will Snapchat's new update stop people from sexting using the app? ' (Telegraph, September 2015), Snapchat gained early notoriety as the so-called app built for 'sexting', its quick-to-vanish imagery being seen as the ideal medium for transmitting explicit content (see, for example, Poltash 2013; Roesner et al 2014; Utz et al 2015). Returning to the 'Freak of the week' song lyrics above, Snapchat has become embedded in a sexual lexicon adapted to account for time, documentation and memory.…”
Section: Stories Snaps and Screenshots: What Is Snapchat?mentioning
confidence: 99%
See 1 more Smart Citation
“…it was found that women are more involved in these activities when they feel jealous (Muise, Christofides, & Desmarais, 2014). However, it was found that snapchat can produce more jealousy than Facebook as compared to other social networks, thereby paving the pathway to other forms of interactions and data collection (Utz, Muscanell, & Khalid, 2015).…”
Section: Sociocultural Variablesmentioning
confidence: 99%
“…The virtual worlds created by modern technology are fertile grounds to test the explanatory power of such fundamental tenets of evolutionary theory. One such theory, sex differences in jealousy manifestation (Buss 2000;Buss et al 1992), can be explored by accessing social media such as Facebook and Snapchat (Utz et al 2015) or by measuring reaction to infidelity-revealing mobile phone messages (Dunn and McLean 2015). There are currently a staggering 1.94 billion active Facebook users worldwide, 1.15 billion of which are active daily and this figure continues to rise relentlessly (Facebook,5 March 17).…”
Section: Introductionmentioning
confidence: 99%